Desenvolvimento de aplicativo móvel sobre vacinação infantil para pais - Paula, Thais Rodrigues (2019)
Given the potential use of health applications, constant changes in the vaccination schedule and the need to increase adherence to childhood vaccines, this study aimed to develop a mobile application on child vaccination for parents. It was a methodological research, of technological production, involving construction and evaluation. The first was developed from February 2018 to March 2019, in four stages: Modeling, performing the application planning and the survey of applications on the Android and iOS virtual platforms; Navigation project, with the application structure and the first prototyping; Abstract design of the interface, in which the application's new visual identity, logo and name definition were applied; Implementation, in which the application was concretized with the version to be evaluated. There were 71 APKs of test release versions until reaching the final version of PROimuni, made up of 20 screens contemplating vaccine card, vaccine information, vaccine calendar, geolocation, frequently asked questions. Twenty-two nurse judges and nine Information and Communication Technologies judges participated in the evaluation. They used instruments containing categories such as: objectives, content, presentation, installation, functionality, usability, interface, and interactivity. In addition to the judges, 22 mothers analyzed aspects such as: objectives, appearance, structure, usability, efficiency and interactivity. Data collection took place from April to July 2019, via online. All form items were assessed from the Likert scale: 1) Strongly disagree; 2) Partially disagree; 3) Indifferent; 4) I partially agree; 5) I totally agree. A dichotomous variable was created, considering them as adequate (4 and 5) and inappropriate (1, 2 and 3). The software was analyzed based on the proportion of subjects who considered the appropriate items. For this, a proportion equal to or greater than 0.85 in the confidence intervals, obtained through prop.test, calculated by Software R was considered. Regarding the consistency of the responses of nurses, ICT judges and target audience, we obtained if a Cronbach's alpha of 0.86; 0.96 and 0.91 respectively. In the nurses' evaluation, all items in the Objective and Content categories were considered adequate, but 14 of 22 judges rated 1 item as inadequate in the Presentation category, with a CI between 0.40 and 0.81. Regarding the evaluation of the ICT judges, the items in the Objective category were adequate, however, 3 items were inadequate, 2 in the Installation and Functionality category (2.8 - CI 0.15 to 0.77 and 2.9 - CI 0.22). 0.84) and 1 of Usability and Interface (3.12 - CI from 0.09 to 0.69). All items evaluated by the target audience were judged as appropriate. It is noteworthy that items in which the confidence interval is not included in the ideal proportion of 0.85 will be reviewed, as well as those that were the subject of suggestions. The potential of this tool for vaccine management and adherence is believed to contribute to the promotion of child health.